Fine particle migration and collection in a wet electrostatic precipitator. (3rd April 2017) - Yang, Zhengda; Zheng, Chenghang; Chang, Qianyun; Wan, Yi; Wang, Yi; Gao, Xiang; Cen, Kefa
ABSTRACT: Electrostatic precipitation is considered as an effective technology for fine particle removal. A lab-scale wet electrostatic precipitator (ESP) with wire-to-plate configuration was developed to study particle migration and collection. The performance of the wet ESP was evaluated in terms of the corona discharge characteristics, total removal efficiency and fractional removal efficiency. The corona discharge characteristics and particle removal abilities of the wet ESP were investigated and compared with dry ESP. Particle removal efficiency was influenced by discharge electrode type, SO2 concentration, specific collection area (SCA) and particle/droplet interaction. Results showed that the particle removal efficiency of wet ESP was elevated to 97.86% from 93.75% of dry ESP. Three types of discharge electrodes were investigated. Higher particle removal efficiency and larger migration velocity could be obtained with fishbone electrode. Particle removal efficiency decreased by 2.87% when SO2 concentration increased from 0 ppm to 43 ppm as a result of the suppression of corona discharge and particle charging. The removal efficiency increased with higher SCA, but it changed by only 0.71% with the SCA increasing from 25.0 m 2 /(m 3 /s) to 32.5 m 2 /(m 3 /s). Meanwhile, the increasing of particle and droplet concentration was favorable to the particle aggregation and improved particle removal efficiency. Implications : This work tends to study the particle migration and collection under spraying condition. The performance of a wet electrostatic precipitator (ESP) is evaluated in terms of the corona discharge characteristics, total particle removal efficiency, and fractional particle removal efficiency. The effects of water droplets on particle removal, especially on removal of particles with different sizes, is investigated. The optimization work was done to determine appropriate water consumption, discharge electrode type, and specific collection area, which can provide a basis for wet ESP design and application.